Evaluation of a community health worker training program in rural Appalachia, USA - Miller, Wayne C. (International Journal of Medicine, 2015)
Background: Limited support for healthcare services is one reason rural Appalachia is among the unhealthiest regions in the United States.Objective: Evaluate Level 1 of a multi-level community health worker (CHW) training program designed to train CHWs easily so they can affect community health.Methods: 198 CHWs evaluated their training curriculum. CHW activities were tracked for 19 months. Group data were analyzed with t-tests and ANOVA using mean Â± SEM comparisons. Correlation coefficients and rank sum difference analyses were used to evaluate ranked variables. Statistical significance was set at p<0.05.Results: Excellent or good rankings were given by 100% of CHWs for their instructorâ€™s knowledge, 100% being treated fairly, 99% overall class rating, 97% fairness of exam, 96% course objectives met, and 92% course manual. CHW test performance did not affect any variable. CHWs were only asked one question every two months they could not answer. CHWs talked to four new people each month, two people a month for multiple visits, and three people a month for follow-up visits.Conclusions: No need to change the CHW curriculum, training materials, or testing procedures. A 15-hour CHW training program is adequate enough to provide valid healthcare service support in rural Appalachia, USA.